Aprendizagem da docência por homologia: experiências formativas no Programa de Bolsas em Monitoria (PBM) - Alves, Ingrid da Silva (2025)
This dissertation addresses the learning resulting from formative experiences in the relationship with university professors, highlighting the contributions of the Monitoring Scholarship Program. The main objective is to understand formative experiences in university teaching through the homological action of the practices developed during the participation in the Monitoring Scholarship Program of the State University of Feira de Santana (UEFS). The research adopted the principles of qualitative research in the (auto)biographical approach, using narrative interviews as a research device. The study was conducted in the academic environment, specifically in an institution that is part of the Monitoring Scholarship Program, with the participation of five collaborators who participated in the Monitoring Scholarship Program. The analyses were inspired by the comprehensive-interpretative method. Therefore, this dissertation work revealed that PBM is the means that provides a condition for student monitors to experience the daily life of the university and understand how teaching is presented in practice in their real contexts. Thus, inserting a student-monitor in the training process will make him understand that the university is composed of elements that give meaning to the teaching work through the temporal context of learning